Probing functional group dependence in dissociative electron attachment using negative ion momentum imaging. Issue 13 (January 2020) - Gokhale, S; Gope, K; Tadsare, V; Bain, M; Raghav, A; Ashfold, M N R; Krishnakumar, E; Prabhudesai, V S
Synopsis: Dissociative electron attachment (DEA) is the most efficient way to explore the structure and dynam-ics of excited states of molecular negative ions. More importantly, DEA has been shown to be a tool for chemical control. One crucial aspect of the chemical control using DEA is the functional group dependence present in this process. Here we present cases on the effect of delocalized electrons on DEA patterns observed in simple aromatic compounds.